Physical properties of raw milk and the relation between sanitation and hygiene of milk and listeria monocytogenes contamination on the farm people in sinjai district of South Sulawesi - F. Yuliati; R. Malaka; K. I. Prahesti; E. Murpiningrum (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2015)
Listeria monocytogenes is pathogenic bacteria causing disease outbreaks of food origin (food borne bacterial disease) that causes listeriosis in susceptible individuals. Listeria monocytogenes often easily contaminate milk and other livestock products. The aim of the research was to know the physical properties of raw milk and the relation between sanitation and hygiene of milk and Listeria monocytogenes contamination on the dairy farm in Sinjai District South of Sulawesi. In this research, eight samples of fresh milk were taken from local dairy farm. A direct observation was performed on the hygiene and the cage sanitation during milk processing. Then, the physical quality of the milk (specivic gravity, alcohol test, organoleptic examination, acidity). Listeria monocytogenes was detected by culturing on Listeria Selective Agar (LSA) media. The results of study showed that raw milk was contaminated with Listeria sp. In general, the physical quality of raw milk was satisfactory, however the result of alcohol test of milk showed that it was not so good. The presence of bacteria L. monocytogenes in the milk did not cause physical changes either in color, smell, consistency, acidity, or specific gravity. The contamination was closely related to the condition of hygiene and cage sanitation during the milk processing.